Legal Support for Sustainable Agroecological Development: Evidence from Ukraine - Novak , Tamara; Melnyk , Victoria; Kovalchuk , Inna; Pakhomova, Anna; Nastina, Olga (European Journal of Sustainable Development, 2024)
This article is dedicated to characterizing laws regarding Ukrainian agroecological development. Researched existing approaches to the interpretation of the concepts of "agroecology", "ecologization of agricultural production", "agroecological law", "sustainable development". Definition of the category of "agroecological development" is formulated. It is determined that in modern Ukrainian realities the weight of international acts in the implementation of agroecological development has significantly increased. This stems from the European integration prospects of our country. The need to account for best international practices in regulating the functioning of both modern and post-war agriculture. It is established that Ukraine has already developed a fairly solid legal framework that establishes environmental requirements for agricultural production. Further effective application of these requirements depends on the formation of the state agrarian policy and the planning and implementation of agro-ecological measures at the local and regional levels. Therefore, an update of documents regarding development of Ukrainian economy and agricultural sector for the period up to 2030. Key measures for agroecological development at the regional level have been identified, which is recommended to be included in local programs of economic development. Keywords: agriculture, agricultural production, legal support, sustainable development, greening of agricultural production, agroecology, agrarian policy.